Diseño 3D aplicado a la visualidad de espacios partiendo de la abstracción iconográfica de cerámicas. - Toaquiza Lema, María Elena (2024)
This research focused on the application of 3D modeling to interior design and renovation, with the objective of developing an effective and adaptable methodology for companies of different sizes seeking realistic and executable visual proposals to aesthetically and functionally renovate their spaces. The project was conducted at Hotel Zeus in Riobamba, a prominent hotel company with over 36 years of experience in the industry, which features a restaurant on the ground floor of its building. The goal was to update the restaurant’s design to reflect a national Andean concept while preserving the elegance and minimalism that characterize the hotel’s corporate image. The inspiration for conceptualizing the Andean style concept was drawn from the collection of national ceramic pieces displayed on the upper floors of the hotel. These pieces underwent iconographic analysis and modular abstraction based on Erwin Panofsky and Saussure's methodologies. The restaurant redesign was executed using advanced 3D modeling and rendering tools, including Blender and Twinmotion, which enabled the creation of precise, high-quality visual representations. The project aimed not only to enhance the aesthetics and functionality of the restaurant but also to strengthen the cultural identity of the hotel, providing guests with a unique and enriching experience and fostering greater brand loyalty. Furthermore, the integration of advanced technologies such as 3D modeling in the hotel industry was presented as a case study for future innovations in the sector, demonstrating the value of combining tradition and modernity in space design. This approach not only elevates the hotel’s value proposition in the tourism market but also establishes a standard for the use of digital tools in interior design.